Sustainable Innovations in Recycled Textiles - Muthu, Subramanian Senthilkannan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book highlights the environmental and economic benefits of recycling in textiles and fashion; vis-a-vis virgin textiles. Recycling plays an inevitable part when it comes to sustainable innovations in textiles and fashion sector. As basic information pertaining to the benefits, challenges of recycling in textiles are discussed to the sufficient extent in the literature, this book deals with the innovative at the same time, sustainable products made from the recycled textiles.
Recycled Cotton from Denim Cut Waste -- Sustainable apparel production from recycled fabric waste -- An Avant-Garde Collection Inspired by the Global Water Crisis: Recycling Waste to Aesthetic Garments.
Keywords: Manufactures; Environmental chemistry; Business logistics; Materials -- Analysis; Industrial engineering; Production engineering; Chemistry, Technical; Machines, Tools, Processes; Environmental Chemistry; Supply Chain Management; Characterization and Analytical Technique; Industrial and Production Engineering; Industrial Chemistry